Double-Core Model of Intelligent Pipe and Intelligent Management to Realize Flow Management - Yizhi Ding; Haidong Cui (Dianxin kexue)
In order to follow the development trend of mobile internet and improve business income, it is necessary for communication operators to push flow management completely. A typical business scene about flow management was analyzed, a kind of double-core model related to intelligent pipe and intelligent management to realize flow management was proposed and a realization mechanism of model was given. This mode is mainly made up of pipe control node and management platform node. It is verified by the application result of project experiment that this model can support communication operators to realize flow management efficiently.